Validation Tool forE-government in Malaysia Based on MAMPU Guidelines - Abdul Wahab, Mohd Faris (Universiti Teknologi PETRONAS, 2009)
Malaysian government has introduced MAMPU guidelines to the government agencies which it is used as the main guiding principle in developing and maintaining their websites. All government agencies websites must compliances with MAMPU guidelines. A validation tool was created to validate whether the website is compliance or not with the guidelines. However, previous validation tool only check the compulsory criteria of the MAMPU guidelines. It also does not provide any suggestion for each error after validating the website. This project is to enhance that validation tool by adding the additional criteria and to validate government websites (Ministry of Education Malaysia and Minister of Culture, Arts and Tourism Malaysia) using the developed validation tool against human validation. Human evaluation process consists of a set of instructions based on the specific task scenario. The project will append the additional criteria (6.3.2 a, 6.3.2 b) on the MAMPU guidelines which provide supported link such as help, trouble shooting and guidelines on how to interact with the website and also provide some useful video or audio which are related to the agency's services. Methodology used in developing and enhancing current validation tool is prototyping-based methodology. Analysis, design and implementation are performed repeatedly. The result will be a new validation tool which consists of both compulsory and additional criteria based on MAMPU guidelines and also the alternative ways to check the website instead of key in the URL. Finally, this project is hoped to assist government in improving Malaysia's position in World £-Government ranking as well as save cost, time and effort in validating each website.